Identificação das perdas do processo produtivo na fabricação de massas alimentícias: um estudo baseado em sistemas de custos - Brum, Danielli Vacari de (2006)
The competition incited among the companies comes debtor them to improve it its productive systems of permanent form, fighting all and any occured loss. This work has as main objective the identification of the losses in the production of nourishing pasta of a company, based on systems of costs. The principle of used expenditure was of ideal absorption. For the determination of the losses, a treatment differentiated how much to the used resources was necessary. A separation between the changeable costs and the fixed costs was made. The use of standards of consumption of changeable resources and efficient taxes of consumption of fixed resources, in function of an installed capacity had constituted the base of the system for the determination of the cost of the losses. A time identified the main causes of these losses, had been suggested some actions of improvement, so that the main problems could be cured and/or be minimized. After that some pointers had been suggested to follow the effectiveness of the implemented actions. Finally, it was concluded that the considered system allows to take action fast and to work with financial and operational measures, simultaneously, facilitating the accompaniment of the process.